Rancang Bangun Alat Purifikasi Biogas Water Scrubber Berbasis Mikrokontroler - Farradina Choria Suci (Politeknik Negeri Jakarta, 2020)
Biogas is one of the potential renewable energies to be developed in Indonesia. Biogas contains CH4 as the primary element, besides containing impurities such as H2S and CO2. The presence of these gases can reduce the quality of biogas and can cause corrosion in equipment. Therefore, it is necessary to purify the gas content, one of them by using a water scrubber. Purification of CO2 and H2S gas levels by using a water scrubber is a physical purification. Purification can also be done chemically, one of them by using CaO. In this research, the media used to make biogas were water hyacinth, cow dung and vegetables, while the media for purification used wood sawdust pellets, quicklime pellets (CaO) and mixed lime and wood lime pellets. The purification process was divided into 3 experiments, the best result was the third experiment with the percentage of biogas production by 15 kg of vegetables with 7.5 kg of cow dung and 15 liters of water, and adding EM-4 by 5%. The results showed the greatest reduction in CO2 gas with a water scrubber media of 54% while the largest H2S gas value with a water scrubber media with CaO and sawdust by 66%.